Asymmetric catalytic alkynylation of thiazolones and azlactones for synthesis of quaternary α-amino acid precursors. Issue 23 (25th May 2021) - Meng, Beibei; Shi, Qian; Meng, Yuan; Chen, Jie; Cao, Weiguo; Wu, Xiaoyu
Abstract : Under 5 mol% of phosphonium salt catalyst derived from chiral amino alcohol, asymmetric alkynylation of thiazolones and azlactones has been developed. Abstract : Asymmetric alkynylation of thiazolones and azlactones with alkynylbenziodoxolones as the electrophilic alkyne source catalyzed by thiourea phosphonium salt is described. By using thiazolones as nucleophiles, the desired alkyne functionalized thiazolones were obtained in 55–89% yields with 31–86% ee. Azlactones gave the desired products in comparable yields with lower enantioselectivities. Ring-opening of the alkynylation products led to α, α-disubstituted α-amino acid derivatives efficiently without loss of enantioselectivity.